Molecular analysis of invasive Cichla (Perciformes: Cichlidae) populations from neotropical ecosystems. (June 2017) - Diamante, Nathália Alves; de Oliveira, Alessandra Valéria; Petry, Ana Cristina; Catelani, Paula Araújo; Pelicice, Fernando Mayer; Prioli, Sônia Maria Alves Pinto; Prioli, Alberto José
Abstract: Invasive Cichla populations in the São João River basin were genetically analysed and compared with Cichla populations from other neotropical hydrographic basins. Polymorphic sequences within the mitochondrial DNA D-loop region confirmed the introduction of different populations to the regions under analysis. Cichla kelberi was introduced to the Juturnaíba reservoir and a downstream area of the São João River, with Cichla monoculus restricted to downstream river areas. Results from this study will be useful for monitoring invasive Cichla populations in the coastal basin since it elucidated the taxonomic units in the reservoir and an areas downstream.